Strip cropping system as a climate adaptation strategy in semi-arid Alfisols of South Central India - MARUTHI, V; REDDY, K S; PANKAJ, P K (The Indian Journal of Agricultural Sciences, 2017)
A two year (2013-2015) field experiment was conducted to assess the efficiency of rainfed strip intercropping of sorghum (S) and pigeonpea (PP) under 4:4 replacement series in comparison with 2:1 intercropping under additive series for system productivity, economic efficiency and farm family food security. There were three treatment combinations (S+ PP –relay horsegram (HG), S+ PP -ratoon S and S+ PP -sequence HG) accommodating an opportune crop of relay or sequence HG to be tested against checks of sole crops. S and PP strip system in a high rainfall year (2013) yielded 31% higher grain than 2:1 S and PP intercropping, but such advantages were not observed during a deficit rainfall year (2014). Significant PP yield increase during a high rainfall year in a strip system increased both water productivity (10.1 to 16.5 kg/ha/mm) and net returns (Reupees 57490 to 71680/year). Similarly, during high rainfall year (2013), a superior diverse index (1.63 over 1.19) and production efficiency (19.6 over 13.5 kg/ha/day) was observed. Both relay/sequence cropped HG performed equally well while ratoon S performed poorly. Therefore, for changing climate, 4:4 strip intercropping of S and PP showed higher productivity and economic returns as compared to 2:1 intercropping system. Opportune cropping through relay or sequence HG can be successfully carried out in semi-arid regions during post monsoon season for climate change adaptation.